2014
DOI: 10.1007/s12035-014-8899-y
|View full text |Cite|
|
Sign up to set email alerts
|

Neuroprotective Role of Novel Triazine Derivatives by Activating Wnt/β Catenin Signaling Pathway in Rodent Models of Alzheimer’s Disease

Abstract: It has been reported in the literature that cholinesterase inhibitors provide protection in Alzheimer's disease (AD). Recent reports have implicated triazine derivatives as cholinesterase inhibitors. These findings led us to investigate anti-cholinestrase property of some novel triazine derivatives synthesized in this laboratory. In vitro cholinesterase inhibition assay was performed using Ellman method. The potent compounds screened out from in vitro assay were further evaluated using scopolamine-induced amne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 60 publications
0
39
0
Order By: Relevance
“…Caspases, a family of thiol proteases, are activated during the neurodegenerative process of AD and play an important regulating role in the apoptotic cascade [37, 38]. A feature of caspases in the cell is that they exist as zymogens, termed pro-caspases, which are inactive until a biochemical change causes their activation [39].…”
Section: Discussionmentioning
confidence: 99%
“…Caspases, a family of thiol proteases, are activated during the neurodegenerative process of AD and play an important regulating role in the apoptotic cascade [37, 38]. A feature of caspases in the cell is that they exist as zymogens, termed pro-caspases, which are inactive until a biochemical change causes their activation [39].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies on 5,6-diaryl triazines showed neuropharmacological applications of this moiety, such as adenosine A 2A antagonism, in Parkinson's disease 31 , anti-neuroinflammatory activity in Alzheimer's disease 32 and as neuroprotectants 33 . More recently, potent neuroprotective action of some 1,2,4-triazines by activating Wnt/b-catenin signaling pathway has been demonstrated by our research group 34 . Some patents have also disclosed the topical anti-inflammatory 35 and antithrombotic activity of diaryl triazines 35 .…”
Section: Introductionmentioning
confidence: 91%
“…Our earlier study has shown that this type of compounds does not exhibit any cytotoxicity rather show protective role in Malondialdehyde (MDA), catalase and intracellular reactive oxygen species (ROS) generation assays 34 . The whole human blood aggregation study was done as per our previously reported procedure 37 .…”
Section: In Vitro Platelet Aggregation Assaymentioning
confidence: 98%
See 1 more Smart Citation
“…[24,25] On the other hands, N-morpholine moiety was recently used in design and synthesis of new AChE inhibitors (Figure 1, C). [26] Hence, in continuation to our interest in the development of potent anti-Alzheimer agents by molecular hybridization, in this work, a novel series of coumarin-3-carboxamide-N-morpholine hybrids 5a-5l has been presented ( Figure 1). [27] Herein, the synthesis, AChE/BuChE inhibitory effects, kinetic, and docking studies of these hybrids as new dual binding site ChE inhibitors are reported.…”
Section: Introductionmentioning
confidence: 99%